Biopolymer Compositions Based on Poly(3-hydroxybutyrate) and Linear Polyurethanes with Aromatic Rings-Preparation and Properties Evaluation - Krzykowska, Beata; Czerniecka-Kubicka, Anna; Białkowska, Anita; Bakar, Mohamed; Kovářová, Miroslava; Sedlařík, Vladimir; Hanusova, Dominika; Zarzyka, Iwona (Polymers, 2024)
Polymer biocompositions of poly(3-hydroxybutyrate) (P3HB) and linear polyurethanes (PU) with aromatic rings were produced by melt-blending at different P3HB/PU weight ratios (100/0, 95/5, 90/10, and 85/15). Polyurethanes have been prepared with 4,4'-diphenylmethane diisocyanate and polyethylene glycols with molar masses of 400 g/mol (PU400), 1000g/mol (PU1000), and 1500 g/mol (PU1500). The compatibility and morphology of the obtained polymer blends were determined by infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and differential scanning calorimetry (DSC). The effect of the polyurethane content in the biocompositions on their thermal stability and mechanical properties was investigated and compared with those of the native P3HB. It was shown that increasing the PU content in P3HB-PU compositions to 10 wt.% leads to an improvement in the mentioned properties. The obtained results demonstrated that the thermal stability and mechanical properties of P3HB were improved, particularly in terms of increasing the degradation temperature, reducing hardness, and increasing impact strength. The best thermal and mechanical properties were shown by the P3HB-PU polymer compositions containing 10 wt.% of polyurethane modifiers, especially PU1000, which was also confirmed by the morphology analysis of these biocompositions. The presence of polyurethanes in the resulting polymer biocomposites decreases their glass transition temperatures, i.e., makes the materials more flexible. The resulting polymer biocompositions have suitable mechanical properties and thermal properties within the processing conditions for the predicted application as biodegradable, short-lived products for agriculture.
Keywords: polyester; polyurethane; thermal properties; structure–properties relationship; mechanical properties